2007
DOI: 10.4028/www.scientific.net/msf.556-557.267
|View full text |Cite
|
Sign up to set email alerts
|

In Situ X-Ray Measurements of Defect Generation during PVT Growth of SiC

Abstract: All rights reserved. No part of contents of this paper may be reproduced or transmitted in any form or by any means without the written permission of Trans Tech Publications Ltd, www.scientific.net.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…One-dimensional beam focusing of hard X-rays by crystals in Laue transmission geometry has been described earlier (Guinier & Tennevin, 1949) and it is being used increasingly for material analysis (Stockmeier et al, 2005;Konias et al, 2007). The method presented here is an extension to a twodimensional focusing with the aim to develop a novel concept for a small-angle diffractometer for high-energy X-rays.…”
Section: Discussionmentioning
confidence: 99%
“…One-dimensional beam focusing of hard X-rays by crystals in Laue transmission geometry has been described earlier (Guinier & Tennevin, 1949) and it is being used increasingly for material analysis (Stockmeier et al, 2005;Konias et al, 2007). The method presented here is an extension to a twodimensional focusing with the aim to develop a novel concept for a small-angle diffractometer for high-energy X-rays.…”
Section: Discussionmentioning
confidence: 99%
“…To trace the SiC resublimation paths and to link it with numerical modeling of the growth process, Si 13 C was added to the bottom of Si 12 C powder source . Experiments that include in situ X‐ray diffraction during PVT growth have been reported in .…”
Section: Growth Process Visualizationmentioning
confidence: 99%
“…It was experimentally shown that p‐type SiC crystal boules systematically exhibit a reduced basal plane dislocation density which is beneficial for bipolar SiC electronic devices. Although not completely understood from fundamental growth theory, the electronic properties of p‐type SiC, in particular the position of the Fermi energy below the band gap center, have been attributed to the reduction of the basal plane dislocation density .…”
Section: Dopingmentioning
confidence: 99%
“…The application of X-ray technology at our department for in-situ visualization of the SiC crystal in the PVT reactor has lead in recent years to several important results on mass transport, polytype switching and defect generation. There are several publications about gaining 2-D X-ray radiography and X-ray diffraction images from the crystal during growth [1][2][3][4][5], which improved the basic understanding of silicon carbide crystal growth. Based on past research, our goal is to significantly improve the image quality by using 3-D X-ray computed tomography.…”
Section: Introductionmentioning
confidence: 99%